ANALISIS TINGKAT EFISIENSI DAN OUTCOME PELAYANAN DI RS AISYAH SITI FATIMAH SIDOARJO SELAMA PANDEMI COVID-19 - Umi Khoirun Nisak; Titin Wahyuni; Nova Mellania; Cholifah . (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
Background: Hospitals during the COVID-19 pandemic are trying hard to reduce the number of deaths and losses of COVID-19. Analysis of hospital efficiency and results of hospital services is needed to improve and assess the quality of hospital services provided to patients. In measuring the efficiency of the services provided by the hospital, an analysis of bed use was used through the Barber Johnson chart. To assess the outcome of a service through mortality and morbidity rates. Subjects and Method: This research were descriptive research with data collection by interview to health workers which includes Professional Care Providers (PPA) document study. The research was conducted during August-December 2021. The data obtained were processed into percentage data and Barber Johnson charts. Results: Research Results The mortality rate in June was 24.2% and July 41.7%. Johnson's barber chart is in an inefficient area. BTO in June and July 2021 is 5 and 3, TOI in June and July 2021 is 2.6 and 6.9. Conclusion: Aisyiyah Siti Fatimah Hospital Sidoarjo has not yet entered the efficient area of ??the Barber-Johnson Graph. Mortality and morbidity rates are also high due to the COVID-19 pandemic. Strategies that can be carried out are by increasing the number of available beds during the COVID-19 pandemic as an effort to mitigate the hospital disaster, and improving the addition of supporting equipment for medical services related to COVID-19 so that inpatient services are efficient. Keywords: BOR, Barber Johnson, Mortality, Morbidity